Human neural rosettes secrete bioactive extracellular vesicles enriched in neuronal and glial cellular components - Malena Herrera Lopez; Matías Bertone Arolfo; Mónica Remedi; Laura Gastaldi; Carlos Wilson; Gonzalo G. Guendulain; Danilo Ceschin; Andrés Cardozo Gizzi; Alfredo Cáceres; Ana Lis Moyano (Scientific Reports)
Abstract Extracellular vesicles (EVs) play a critical role in the development of neural cells in the central nervous system (CNS). Human neural rosettes (hNRs) are radial cell structures that assemble from induced pluripotent stem cells (hiPSCs) and recapitulate some stages of neural tube morphogenesis. Here we show that hiPSCs and hNRs secrete EVs (hiPSC-EVs and hNR-EVs) with distinctive protein cargoes. Remarkably, hNR-EVs carry neuronal and glial cellular components involved in human CNS development. Importantly, hNR-EVs stimulate stem cells to change their cellular morphology and promote neurite growth in human and murine neurons with a significant dysregulation of SOX2 levels. This transcription factor modulates both neural differentiation and pluripotency. Interestingly, these effects were inhibited by antibodies against an unexpected neuroglial cargo of hNR-EVs: the major proteolipid protein (PLP). These findings show that hNRs secrete bioactive EVs containing neural components and might contribute as trophic factors during human neurodevelopment.